Socialization and Education of Maggot Extract Nanogel Preparations (Hermatia illucens) for Wound Healing - Marbun, Romauli Anna; Sihombing, Yanna Rotua; Anggraeni, Ratih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Wounds are damage to skin tissue that can disrupt the body's protective function and are susceptible to infection. Based on data from the 2017 Basic Health Research, the prevalence of wounds in Indonesia reached 8.2% and showed an increasing trend. One alternative method of wound healing that is known to be effective is maggot therapy using Hermetia illucens. However, the use of live larvae often causes disgust, thus inhibiting public acceptance. Objective: to provide socialization and education regarding the use of maggot extract nanogel preparations as an innovative, safe, and more acceptable form of wound treatment for the public. Method: The method used was to conduct direct socialization to pharmacy students at the Medistra Lubuk Pakam Health Institute. The tool used in data measurement was a questionnaire with a pre-test and post-test design. Results and discussion: Nanogel is formulated from maggot extract with various concentrations and has undergone laboratory tests, showing that the formulation with a concentration of 7.5% has the best particle size and high effectiveness in wound healing. These results are presented and each question item in the questionnaire will be answered by participants. The results of the socialization understanding are 90% of students understand the benefits of maggot extract nanogel preparations (Hermatia illucens) for wound healing. The indicator of the success of this socialization is > 80% of students are correct in filling out the questionnaire with a value above > 75. Conclusion: formula III concentration of 7.5% is a recommendation as the best dose for wounds because it meets the standards of preparation evaluation tests and effectiveness tests. Pharmacy students understand and can conduct further research for wound healing from the biomolecular level